EXPERIENCE OF USING SELECTIVE LPS-SORBTION IN THE COMBINED THERAPY OF THOSE SUFFERING FROM GRAM-NEGATIVE SEPSIS - I. V. Bovkun; E. G. Gavrilova; D. V. Sokolov; I. V. Shlyk (Вестник анестезиологии и реаниматологии)
Sepsis remains to be a global medical problem associated with high mortality level. Due to this, there is constant interest towards investigation of its pathogenesis and introduction of new management techniques. Current recommendations contain clear instructions for intensive care including substitutive renal therapy in case of renal dysfunction, however other methods of extracorporal detoxification including selective sorbtion of endotoxin are still being discussed. Goal: to demonstrate the opportunities of selective LPS-sorbtion in the combined therapy of those suffering from septic shock using a specific clinical case. Results: Immediately after selective hemosorption the patient with septic shock demonstrated the following positive changes: reduction of body temperature down to low-grade fever, stabilization of hemodynamic rates, reduction of noradrenaline dose from 0.2 to 0.05 mkg (kg ∙ min-1), reduction of lactate level from 2.3 to 1.7 mmol/L and improvement of respiratory function rates. The renal function improved against the background of stabilization of hemodymanic rates, thus serum creatinine reduced from 0.309 to 0.150 mmol/L. The substitutive renal therapy was fully stopped on the 9th day. The intensity of clinical manifestations of multi-organ dysfunction reduced from 10 to 4 according to SOFA score. Conclusion. Clinical follow-up demonstrated the positive experience of using selective LPS-sorbtion in the combined therapy of septic shock, caused by gram-negative bacteria. Express test for endotoxin activity level in the septic shock patients enhances the objectivity of choice of extracorporal hemocorrection methods.